دور العربون في تخفيف المخاطر في المصارف الإسلامية وتطبيقية المعاصرة /‏‏ - بدني، يوسف آدم (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi Maliziya, 2009)
This research focuses on “The role of down payment ('Arabun) in Islamic banks and its contemporary applications”. The study begins with discussing the concept of 'Arabun, its model, and legality in Islamic Jurisprudence. It also explains the similarities and differences between down payment and some other contracts which look like it. It also explains its concept and legality in both Islamic countries civil laws and Western civil laws. Moreover, the study discusses and explains the concept of risk management in Islamic banks, capitalizing on the most important risks that Islamic banks face in their transactions, and the risks that can be managed by down payment ('Arabun). In addition, it discusses how down payment can be one of the Islamic legal tools in risk management. The study also highlights and explains the similarities and differences between the concept of monitory risk which means the possibility of loss in future, and the concept of risk which is stipulated in the maxims: The benefit of the thing is a return for loss from that thing (Al-kharaj bi al-daman), and The determent is as a return for the benefit (al-ghurm bi al-ghunm). In the final chapter, the study analyzes and explains how 'Arabun can be one of the Islamic legal tools in several contracts and its role in managing its risks, and explains some recent applications in some Islamic Banks in Malaysia. It also analyses the contracts risks of which cannot be managed by it. The study follows inductive, comparative, and analytical methods. It also distributes questionnaire to some Islamic banks in Malaysia. The study has reached to a number of findings, some of them are: 'Arabun is lawful in Islamic jurisprudence. It is also legal in both Islamic countries civil laws and Western civil laws. Down payment ('Arabun) is one of the Islamic lawful tools in risk management in Islamic banks. Moreover, Islamic banks in Malaysia are applying it in their transactions, and it was clear that it is one of the Islamic lawful tools in managing risks. It is possible that many risks can be managed by down payment if the Islamic banks will apply it.